Strict biennial lifecycle and anthropogenic interventions affect temporal genetic differentiation in the endangered endemic plant, Pedicularis hallaisanensis - Kim, Seongjun; Lee, Byoung-Doo; Lee, Chang Woo; Park, Hwan-Joon; Hwang, Jung Eun; Park, Hyeong Bin; Kim, Young-Joong; Jeon, Daeyoung; Yoon, Young-Jun (Frontiers in Plant Science, 2024)
Strict biennials are among the least known lifecycles in plant ecology because of their rarity in nature, and their population genetics still remain unknown. The present study addressed strict biennial lifecycle and associated population genetics of Pedicularis hallaisanensis, an endangered endemic plant in Korea. All P. hallaisanensis individuals were counted in August from 2021 to 2023 at the wild population in Gayasan National Park, and lifecycle and morphological changes were monitored monthly. De novo draft genome and single nucleotide polymorphism (SNP) were used to study the population's genetic structure. P. hallaisanensis strictly required two-year of lifecycle per generation, including 8 and 10 months of growing periods as first-year seedling and second-year adult, respectively. Facultative annual and perennial lifecycles were undetected, which resulted in odd-year and even-year flowering cohorts. Permutational multivariate analysis of variance on the detected 3716 SNPs demonstrated that flowering group (p < 0.005), microhabitat (p < 0.001), and their interaction (p < 0.01) had a significant effect on genetic structure, which was differentiated between odd-year and even-year flowering cohorts. Other cluster analyses also showed that a microhabitat under historical anthropogenic interventions contained lowered genetic diversity due to decreased genetic distance between odd-year and even-year flowering cohorts (p < 0.05). Overall, findings suggest that excessive anthropogenic interventions should be avoided to preserve genetic diversity in the wild P. hallaisanensis population. Moreover, conservation programs on similar biennial plants should collect wild breeds from both odd-year and even-year flowering cohorts to improve genetic diversity of the artificially propagated individuals.